2013
DOI: 10.4236/jst.2013.33014
|View full text |Cite
|
Sign up to set email alerts
|

An Electrochemical Nitrite Sensor Based on a Multilayer Film of Polyoxometalate

Abstract: In this work, we have developed an electrochemical sensor for nitrite detection, based on a polyoxometalate (POM) namely mono-lacunary keggin anion [SiW11O39]8﹣ cited as (SiW11). Electrochemical characterization of SiW11 shows two-step reduction processes, with formal potentials of ﹣0.5 V (I) and ﹣0.68 V (II). Oppositely charged polyelectrolyte (poly (allylamine hydrochloride) (PAH)) and (SiW11) were assembled alternately to modify glassy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 49 publications
(46 reference statements)
0
13
1
Order By: Relevance
“…The CV curve exhibits two pairs of successive redox waves which shows that (SiW 11 ) has two‐step reduction processes, with formal potentials of −0.4 V (I) and −0.6 V (II), which are close to the values found in the literature with a GC electrode 37, 42; these redox waves correspond to the reduction of the tungsten centers within the SiW 11 (W VI →W V ). Compared to our previous results with GC 36, the reduction peak current of SiW 11 obtained on BDD electrode is considerably higher than that on GC electrode, which is ascribed to the high electrical conductivity of BDD surface.…”
Section: Resultscontrasting
confidence: 94%
See 2 more Smart Citations
“…The CV curve exhibits two pairs of successive redox waves which shows that (SiW 11 ) has two‐step reduction processes, with formal potentials of −0.4 V (I) and −0.6 V (II), which are close to the values found in the literature with a GC electrode 37, 42; these redox waves correspond to the reduction of the tungsten centers within the SiW 11 (W VI →W V ). Compared to our previous results with GC 36, the reduction peak current of SiW 11 obtained on BDD electrode is considerably higher than that on GC electrode, which is ascribed to the high electrical conductivity of BDD surface.…”
Section: Resultscontrasting
confidence: 94%
“…Our previous studies showed that the redox process of (SiW 11 ) in acidic solution can be described as follows 36:, …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the development of a rapid electrochemical method for nitrite detection without the sample pretreatment prior to analysis and also no interface from other sources (for instance nitrate, sulfate, bromate ions, and oxygen) is highly important. Recently, various kinds of electrochemical nitrite sensors have been fabricated based on the chemical modification of electrode [12][13][14][15][16][17][18][19][20][21][22][23]. In addition, the electrochemical nitrite sensors usually work under weak acidic medium to obtain high sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…They can go through a multielectron reversible redox process without any structural changes. This property has been exploited in a wide range of applications such as photoelectrocatalysts [11], energy conversion and storage systems [12] and sensors [13,14].…”
Section: Introductionmentioning
confidence: 99%